Hepatitis viruses in Ethiopia: a systematic review and meta-analysis. Issue 1 (December 2016) - Belyhun, Yeshambel; Maier, Melanie; Mulu, Andargachew; Diro, Ermias; Liebert, Uwe
Abstract Background The existing seroepidemiological data on viral hepatitis in Ethiopia showed a wide variation in prevalence pattern and the clinical and public health burden have been underestimated. The aim of this systematic review and meta-analysis was to provide a clear and comprehensive estimation of viral hepatitis epidemiology and the potential clinical burdens in Ethiopia. Methods A comprehensive literature search was carried out from five decades (1968–2015) published studies from biomedical databases; PubMed, Google scholar, Medline and Web of Science. Results The overall pooled prevalence of hepatitis B virus (HBV) was 7.4% (95%CI: 6.5–8.4). The pooled prevalence among subgroups showed 5.2% (95%CI: 3.7–7.4) in human immunodeficiency virus (HIV) infected individuals, 8.0% (95%CI: 5.9–10.7) in community based studies, 8.4% (95%CI: 5.4–12.7) in blood donors, 11.0% (95%CI: 7.5–15.9) in immigrants and 6.9% (95%CI: 5.6–8.5) in other groups. Among study parameters considered during meta-regression analysis, only study years were associated with a decreasing HBV prevalence rate over time. The overall pooled prevalence of anti-hepatitis C virus antibody (anti-HCV) was 3.1% (95%CI: 2.2–4.4). Unlike HBV, the anti-HCV prevalence in HIV infected individuals was higher (5.5%, 95%CI: 3.8–7.8%, p = 0.01) than the prevalence observed in the other subgroup of study population. Although relatively few data were available, hepatitis virus A (HAV), D (HDV) and E (HEV) were also circulated in Ethiopia. Conclusions This review indicates that all types of viral hepatitis origins are endemic in Ethiopia. Adapting a recommended diagnostic and treatment algorithm of viral hepatitis in the routine healthcare systems and implementing prevention and control policies in the general population needs an urgent attention.